(untitled) (The South East European Journal of Economics and Business, 2021)
The causal link between savings and economic growth has been extensively discussed in the economic growth and development literature, but the question of the direction of this link has not yet been clearly defined. The aim of this paper is to determine the direction and intensity of savings causality (components of private savings) and economic growth in Bosnia and Herzegovina. Granger’s causality test, the Toda-Yamamoto procedure, was applied to test for causality between savings and economic growth. The results of Granger’s causality test indicated that there is no causal link between components of private savings with economic growth in Bosnia and Herzegovina. It was found that among the variables there is cointegration, but not causality, which means that the variables have a common stochastic trend. This fully corresponds to the characteristics of the Bosnia and Herzegovina’s economy.